Dose-dependent effect of local treatment of Phyllanthus emblica L. cream on diabetic wound - Liao, Ting-ting; Sukpat, Supakanda; Chansriniyom, Chaisak; Patumraj, Suthiluk (Chulalongkorn Medical Journal, 2022)
Background: Non-healing diabetic ulcers are the most common cause of amputation. Several studies have reported for new, more effective treatments for chronic wounds in diabetic patients. Objective: This study aimed to evaluate the effect of local treatment of Phyllanthus emblica Linn. (PE) on a full-thickness wound model in streptozotocin-induced diabetic mice. Methods: Balb/c mice were divided into five groups: control group (CON), diabetic wounded group (DM, streptozotocin 45 mg/kg i.p. daily for 5 days), diabetic wounded group with daily treatment of different concentrations of PE cream (10%; 100%; and 200%, w/v). Seven days after the diabetic induction, all mice were created bilateral full-thickness excisional skin wounds on the back and received vehicle or PE cream into wound bed. At day 14 post-wounding, the percentage of wound closure (%WC) and the percentage of capillary vascularity (%CV) were determined by using confocal fluorescence microscopy and digital image analysis. Results: The dose-dependent of PE on diabetic wounds were determined by both findings of %WC and %CV. The results showed positive correlation between various doses of topical PE and 14-day %CV post-wound creation (r = 0.7197) (P = 0.0017). The linear regression equation, Y = 0.01788X + 37.35, with R2 = 0.5180, described the relationship between PE doses and CV%. Conclusion: These findings show that local administration of PE cream improved the healing process of diabetic wounds in associated with PE’s angiogenic effect in a dose-dependent manner.